Ujaran Kebencian dalam Kolom Komentar Instagram Tokoh Politik: Analisis Linguistik Forensik - Ema Apriyani; Agustina (Persona: Kajian Bahasa dan Sastra, 2023)
This article discusses hate speech in the Instagram comments column of political figures using forensic linguistic analysis. The aims of this study were (1) to explain the types of hate speech in the comments column on political figures' Instagram, (2) to explain the lingual units used to reveal the types of hate speech in the comments column on political figures' Instagram. This type of research is a qualitative research with descriptive method. The results of this study indicate that the types of hate speech in the Instagram comments column of political figures found in this study consisted of 47 utterances of insults, 9 utterances of defamation, 10 utterances of provocation, 1 utterance of incitement, and 11 utterances of spreading fake news. The most dominant type of hate speech is contempt. Then, the lingual units found in this study were hate speech in the form of 13 utterances of words, hate speech in the form of phrases of 12 utterances, hate speech in the form of clauses of 20 utterances, and hate speech in the form of sentences of 33 utterances. The most dominant lingual units are sentences.